The future of Black Theology of Liberation: Narrative as epistemological resource - Eugene Baron (Verbum et Ecclesia, 2024)
The death of Black Theology of Liberation (BTL) has been announced, and many were invited to the funeral. This article rejects vehemently such a death as a myth, and provides two reasons why such a theology would have a place to address theologising in the world. It firstly argues that BTL attributes its birth through stories. These stories are captured in history; embodied stories that are told. Secondly, it is found in a broader epistemology than that provided by the Enlightenment paradigm. Therefore, it is not only found in conceptual, argumentative discourses, but other forms of knowledge systems, including stories, poetry, and personal storytelling. However, this has still not been equally appreciated and explored. Taking the above two reasons into account, the death of BTL cannot be announced by academics, since they were never the sole custodians thereof, only recipients of the tradition of an oppressed people.